2021
DOI: 10.1016/j.inffus.2021.02.016
|View full text |Cite
|
Sign up to set email alerts
|

An analysis model of diagnosis and treatment for COVID-19 pandemic based on medical information fusion

Abstract: Exploring the complicated relationships underlying the clinical information is essential for the diagnosis and treatment of the Coronavirus Disease 2019 (COVID-19). Currently, few approaches are mature enough to show operational impact. Based on electronic medical records (EMRs) of 570 COVID-19 inpatients, we proposed an analysis model of diagnosis and treatment for COVID-19 based on the machine learning algorithms and complex networks. Introducing the medical information fusion, we constructed the heterogeneo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 45 publications
0
13
0
Order By: Relevance
“…The simulations showed that the proposed framework was highly efficient for diagnosing and predicting life-threatening diseases. Fang et al [19] presented a medical information fusion-based diagnostic framework for the treatment of COVID-19 disease. The proposed methodology could improve classification accuracy more than the traditional methods and help healthcare professionals combat COVID-19.…”
Section: Related Workmentioning
confidence: 99%
“…The simulations showed that the proposed framework was highly efficient for diagnosing and predicting life-threatening diseases. Fang et al [19] presented a medical information fusion-based diagnostic framework for the treatment of COVID-19 disease. The proposed methodology could improve classification accuracy more than the traditional methods and help healthcare professionals combat COVID-19.…”
Section: Related Workmentioning
confidence: 99%
“…Pinter et al [106] Multi-layered perceptron Predictions of mortality rate and infected cases Aminu et al [107] Deep neural networks Detection of people with COVID-19 Magar et al [108] Ensemble techniques Virus-antibody sequence analysis and patients' Identification Zeng et al [109] Extreme Gradient Boosting (XGBoost) Forecasting of patient survival probability Ashraf et al [110] Machine & deep learning models Predict the severity of disease or chances of death Shah et al [111] Convolutional neural network (CNN) COVID-19 detection from X-ray images Prakash et al [112] Autoregressive Integrated Moving Average Impact analysis of various policies Rathod et al [113] AI Prediction models Effective crisis preparedness and management Ullah et al [114] Logistic Regression and Support Vector Machine Classification of patients with/without COVID-19 Rathod et al [115] SVM, RProp, and Decision tree Detection of abnormal data for effective analysis Hu et al [116] Spectral Clustering (SC) algorithm Feasible analysis model for the treatment & diagnosis Rashed et al [117] Long short-term memory (LSTM) network Provides public awareness about the risks of COVID-19 Singh et al [118] ResNet152V2 and VGG16 CNN Reduce the high false-negative results of the RT-PCR Saverino et al [119] Digital and artificial intelligence platform (DAIP) Changes implementation in rehabilitation services Peddinti et al [120] Convolutional Neural Network (CNN) Detection of COVID-19 cases in public places Malla et al [121] Ensemble deep learning model Real-time sentiment analysis of COVID-19 data Lella et al [122] Convolutional Neural Network (CNN) model Respiratory sound classification for patient identification Haleem et al [123] Artificial neuronal networks (ANN) Predictions of survival of COVID-19 patients Hashimi et al [124] Deep learning models Tracking and identifying potential virus spreaders Amaral et al [125] Artificial neuronal networks (ANN) forecasting and monitoring the progress of Covid-19 Zgheib et al [126] Collection of ensemble learning methods Detecting COVID-19 virus based on patient's demographics Ferrari et al [127] Bayesian framework Predictions about the behavior of the COVID-19 epidemic Almalki et al [128] COVID Inception-ResNet model (CoVIRNet) Automatic diagnosis of the COVID-19 patients Umair et al …”
Section: Ai Technique Used Purpose In the Context Of Covid-19 Pandemicmentioning
confidence: 99%
“…The complex network theory has been proved to provide a unique opportunity to objectively uncover the inner topology relationships of multi-dimensional data from a global view ( Baggio et al., 2021 ; Qiao et al., 2019 ). Hu et al. (2021) built a heterogeneous information network to uncover the complicated relationships in the syndromes, symptoms, and medicines, aiming to support the COVID-19 diagnosis and treatment analysis.…”
Section: Introductionmentioning
confidence: 99%